The Incredible Hulk Annual 2005 - Panini Books (Panini Books, 1998)
Explores what strength is and how it can be developed using a comic book character, the Incredible Hulk, to demonstrate, and provides information on that character and how he came to be.
Keywords: Intermediate; Juvenile Nonfiction; Readers